Role of service quality in improving customer loyalty towards telecom companies in Hungary during the COVID-19 pandemic - Farheen Naz; Ayman Alshaabani; Ildikó Rudnák; Róbert Magda (Economies, 2021)
The telecommunication sector is one of the most rapidly growing sectors in the world. The COVID-19 pandemic has created an increased dependence of customers on telecommunications to continue their work and studies. The increased usage of internet and telecom services during the COVID-19 pandemic has brought many risks and challenges for the telecom companies to meet the requirements of the consumers. In this regard, it is crucial to understand the factors affecting customer loyalty towards telecom companies during the COVID-19 pandemic. This study is conducted to evaluate the effect of service quality, perception towards promotional packages, and customer delight on customer loyalty towards telecom companies in Hungary. The study also examined the mediating role of customer delight and perception towards promotional packages between service quality and customer loyalty. Another aim of the study is to compare the behavior of Hungarian customers and foreign customers living in Hungary towards telecom companies in the course of the COVID-19 pandemic. The study used a linear snowball sampling method and a well-structured questionnaire to collect the data. In total, 589 completed responses were used for analysis out, of which 208 responses are from Hungarian customers and 381 are from foreigners. To analyze the collected data, regression analysis was applied by using AMOS 22 package. The results of our study revealed that service quality and perception towards promotional packages positively influence customer loyalty among both Hungarian and foreign customers. On the other hand, customer delight significantly influences customer loyalty only among foreign customers. The results also proved the mediating role of promotional packages and customer delight between service quality and customer delight. This study will provide significant practical implications for managers of telecom companies in Hungary.
Keywords: 330; COVID-19; customer loyalty; promotional packages; service quality; telecommunications